VD_FINDINFO ML / 2012 / 4 vom 1. Februar 2012 - VD Tribunal cantonal (2012)
DROIT D'ÊTRE ENTENDU, DROIT DE S'EXPLIQUER, RÉPLIQUE, EXCEPTIONMOYEN DE DÉFENSE | 6 CEDH, 29 al. 2 Cst., 81 al. 2 LP, 50 LVLP